A162 EXPULSION OF THE TAPEWORM HYMENOLEPIS DIMINUTA FROM MICE OCCURS INDEPENDENT OF SEROTONERIC SIGNALLING. (15th March 2019) - Wang, S J; Sharkey, K A; McKay, D M; Wang, A; Wallace, L
Abstract: Background: Helminth infestation is a global concern: millions of individuals suffer acute or chronic infections and the impact on domestic livestock is immense, where anthelminthic resistance is widespread. There are several components to the response against helminth parasites, the best-studied being Th2 immunity. Serotonin (5-HT), a signalling molecule of which 95% is produced in the gut, plays many roles in immunity and gut physiology. Enteric 5-HT content or 5-HT+ enterochromaffin (EC) cell numbers can be increased in response to infection with a helminth parasite. The relevance of these increases and their role, if any, in protection against helminths is unclear. Aims: Using infection with the rat tapeworm Hymenolepis diminuta in the non-permissive mouse host, we sought to determine: 1) changes in 5-HT content and 5-HT immunoreactive EC cell number in intestine; and, 2) the role of 5-HT in the Th2 immune response elicited by H. diminuta. Methods: Male BALB/c mice were infected with 5 cysticercoids of H. diminuta ± i.p. PBS or para-chlorophenylalanine (PCPA; 300 mg/kg, daily for 6 days), a tryptophan hydroxylase inhibitor, to inhibit 5-HT production. At necropsy at 8 or 11 days post-infection, worms were flushed from the small intestine and counted, and intestines and spleens were collected. 5-HT immunoreactive EC cells were identified by immunohistochemistry and 5-HT content in the bowel determined by ELISA. Splenocytes were stimulated with concanavalin A (2 μg/mL, 48h), supernatants were collected and IL-4, IL-5, and IL-10 measured by ELISA. Results: Infection with H. diminuta resulted in increased splenic Th2 cytokine levels at days 8 and 11 post-infection; however, increases in 5-HT+ EC cells were not detected in the gut. Further, while infection with H. diminuta did not affect ileal 5-HT content at day 8 post infection, and contrary to observations in other rodent-helminth model systems, 5-HT levels were reduced in the ileum at 11 days post-infection. PCPA treatment depleted ileal 5-HT content, and this impacted neither the successful expulsion of H. diminuta nor the development (kinetics, magnitude) of Th2 immunity. Conclusions: These data indicate that serotonergic signalling is not essential to expel H. diminuta or the Th2 immune response evoked in response to infection. Whether this is restricted to H. diminuta or generally applicable to flatworm parasites needs to be determined in the future. Funding Agencies: CIHRNSERC, NSERC CREATE, Henry Koopmans Memorial Entrance Scholarship